Making thawed universal donor plasma available rapidly for massively bleeding trauma patients: experience from the Pragmatic, Randomized Optimal Platelets and Plasma Ratios (PROPPR) trial. Issue 6 (30th March 2015) - Novak, Deborah J.; Bai, Yu; Cooke, Rhonda K.; Marques, Marisa B.; Fontaine, Magali J.; Gottschall, Jerome L.; Carey, Patricia M.; Scanlan, Richard M.; Fiebig, Eberhard W.; Shulman, Ira A.; Nelson, Janice M.; Flax, Sherri; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The Pragmatic, Randomized Optimal Platelets and Plasma Ratios (PROPPR) trial was a randomized clinical trial comparing survival after transfusion of two different blood component ratios for emergency resuscitation of traumatic massive hemorrhage. Transfusion services supporting the study were expected to provide thawed plasma, platelets, and red blood cells within 10 minutes of request. STUDY DESIGN AND METHODS At the 12 Level 1 trauma centers participating in PROPPR, blood components transfused and delivery times were tabulated, with a focus on universal donor (UD) plasma management. The adequacy of site plans was assessed by comparing the bedside blood availability times to study goals and the new American College of Surgeons guidelines. RESULTS Eleven of 12 sites were able to consistently deliver 6 units of thawed UD plasma to their trauma‐receiving unit within 10 minutes and 12 units in 20 minutes. Three sites used blood group A plasma instead of AB for massive transfusion without complications. Approximately 4700 units of plasma were given to the 680 patients enrolled in the trial. No site experienced shortages of AB plasma that limited enrollment. Two of 12 sites reported wastage of thawed AB plasma approaching 25% of AB plasma prepared. CONCLUSION Delivering UD plasma to massively hemorrhaging patients was accomplished consistently and rapidly and without excessive wastage in high‐volume trauma centers. The American College of Surgeons Trauma Quality Improvement Program guidelines for massive transfusion protocol UD plasma availability are practicable in large academic trauma centers. Use of group A plasma in trauma resuscitation needs further study.